KEINOVATIFAN PEREMPUAN DALAM PERSPEKTIF KARIR YANG BERPRESTASI - Mukhtar Mukhtar (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2020)
Woman, in their career, are potential. They should do some innovations. Innovations are somewhat like ideas, some things understandable as novel things. The biggest challenges faced by the career-woman are stemming from themselves, namely the intrinsic challenges. As long as they are able to keep this intrinsic challenges with them, they will not be defeated by outside challenges. Consequently, the peak of achievement they achieve is not but the result of their intended innovations.